Wear behavior of heat-treated coated carbon steel - Mat Zaki, Muhammad Zikri; Kamdi, Z.; Ainuddin, A. R.; Hussin, R.; Ibrahim, S. A. (2024)
A particular type of steel has a higher concentration of carbon than other types of steel called carbon steel. This study focused on the electrodeposition coating of Nickel Silicon Carbide (Ni-SiC) composite coating at 50 oC. In this study, medium carbon steel was used as a substrate. 25 g/l SiC was used during the deposition. The carbon steel was acted as the cathode and the carbon rod as an anode during electrodeposition. The coated sample was heat-treated at 350 OC for 1 hour. Scanning Electron Microscope (SEM) was used to analyze the surface morphology and microstructure of the coated and heat-treated sample before and after the wear test. The coated sample's element composition and phase distribution are determined using the Energy Dispersive Spectroscopy (EDS) and X-Ray Diffraction (XRD). To identify the hardness of the composite coating, Vickers micro-hardness test was used on the surface of the sample with 100g load in 10 seconds with ten indentations. Weight loss method was conducted to determine the average wear resistance of the sample. The wear behavior of the Ni-SiC was evaluated using the weight loss method with 3 g/l alumina as the abrasive material. The results showed that the heat-treated coating had higher wear resistance than the without heat treatment. The findings also showed that the sample with the heat-treatment process had a higher hardness. This proved that the heat-treated sample had the best wear behavior and hardness value compared to without heat treatment due to denser coating produced